2000
DOI: 10.1346/ccmn.2000.0480116
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Kinetics of Pentachloroethane by Iron-Bearing Smectites

Abstract: Abstract--The oxidation state of structural Fe greatly alters surface chemistry, which may have a large influence on clay-organic interactions. The effect of structural-iron oxidation state on chlorinated hydrocarbons at the clay-water interface was examined. Pentachloroethane (5CA) was reacted with oxidized, reduced, and reoxidized forms of three different smectites: montmorillonite, ferruginous smectite, and nontronite in aqueous suspension under controlled-atmosphere conditions. Pentachloroethane was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 20 publications
3
30
1
Order By: Relevance
“…Linear regression analysis of the data was performed using analysis of variance (ANOVA) with 95% confidence intervals. The results listed in Table 1 agree with previous work [13,14,19] in that the k obs increases with the reduction of the structural Fe of the clay. The trend of RCl adsorption in the presence of SWa-U ) differed from the trend of RCl…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Linear regression analysis of the data was performed using analysis of variance (ANOVA) with 95% confidence intervals. The results listed in Table 1 agree with previous work [13,14,19] in that the k obs increases with the reduction of the structural Fe of the clay. The trend of RCl adsorption in the presence of SWa-U ) differed from the trend of RCl…”
Section: Resultssupporting
confidence: 90%
“…h ϭ the number of degrees of freedom. vious reports [13,14] The trend in RCl reactivity in the presence of redox-manipulated smectites was compared to the trend in reactivity of RCl in the presence of other Fe(II)-bearing aqueous systems such as iron porphyrins, iron sulfide, or commercial Fe ( Table 4). The trend in reactivity of RCl toward SWa-R displayed acceptable correlation (r 2 ϭ 0.83, p Ͻ 0.5) only with the reported trend in reactivity of RCl toward FeS (10 g/L, t Յ 2,000 h, pH ϭ 8.3 [36,42]).…”
Section: Resultsmentioning
confidence: 99%
“…Surface alkalinity rather than surface acidity, however, may be the more correct surface property accounting for the effect of Fe oxidation state on atrazine sorption/degradation. Cervini‐Silva et al [36] recently reported that the Brønsted basicity of smectite surfaces is greater in the reduced than in the oxidized state. This is attributed to a greater electron density at basal oxygens due to reduction of Fe(III) to Fe(II) in the structure.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, metallic ions play a significant catalytic role during sorption (Cervini-Silva et al, 2000;Saidy et al, 2013). In addition to simple surface sorption, other studies have suggested that encapsulation into micro pore and nano pore spaces can also prevent bacterial enzyme access, aiding the preservation of "metabolizable" OM (Kaiser and Guggenberger, 2007;Curry et al, 2007;Mayer,2004).…”
Section: Introductionmentioning
confidence: 99%